A study on fire safety and awareness among the occupants in Universiti Tunku Abdul Rahman (UTAR), Kampar Campus - Wong, Sammi Jia Chyi (2022)

(untitled)
Fire incident is one of the most disastrous events which can results in severe casualties, environmental impacts, and property loss. In fact, level of fire awareness among the Malaysians are relatively low. The first aim of this study is to evaluate the level of the fire safety and awareness among the occupants in Universiti Tunku Abdul Rahman (UTAR), Kampar Campus. The following aim of study is to determine the relationship between the level of fire awareness with another three variables, which are fire knowledges, human factors in fire safety, and the fire hazards with its consequences by using Pearson Correlation Coefficient. This study was conducted by distributing the prescribed questionnaires to the staffs and students in UTAR, Kampar Campus. There were 389 respondents who had participated in the survey. The data obtained from this study will be analyzed by using SPSS26. The results of Cronbach’s alpha for level of fire awareness, fire knowledge, fire hazards with its consequences, and human factors in fire safety are 0.804, 0.828, 0.835, and 0.665. Based on the results of Pearson correlation, the level of fire awareness is strongly correlated with fire knowledges and fire hazards with its consequences, whereas there is no correlation between human factors with the level of fire awareness. Therefore, the management of UTAR should put more focus on improving the fire knowledge and managing the fire hazard in the campus.